2014
DOI: 10.5194/se-5-741-2014
|View full text |Cite
|
Sign up to set email alerts
|

Plate tectonic raster reconstruction in GPlates

Abstract: Abstract. We describe a novel method implemented in the GPlates plate tectonic reconstruction software to interactively reconstruct arbitrarily high-resolution raster data to past geological times using a rotation model. The approach is based on the projection of geo-referenced raster data into a cube map followed by a reverse projection onto rotated tectonic plates on the surface of the globe. This decouples the rendering of a geo-referenced raster from its reconstruction, providing a number of benefits inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Reconstruction is greatly simplified by using a common georeferencing and projection for all raster data sets. GPlates achieves this by resampling all raster data into a cube map representation (Cannon et al, 2014) immediately prior to reconstruction. Rotated tectonic polygon rendering then references these cube map raster data instead of the original georeferenced raster.…”
Section: Raster Visualizationmentioning
confidence: 99%
“…Reconstruction is greatly simplified by using a common georeferencing and projection for all raster data sets. GPlates achieves this by resampling all raster data into a cube map representation (Cannon et al, 2014) immediately prior to reconstruction. Rotated tectonic polygon rendering then references these cube map raster data instead of the original georeferenced raster.…”
Section: Raster Visualizationmentioning
confidence: 99%
“…The role of the possible complicating factors outlined in the previous section on conjugate margin studies can be evaluated and observed through comparison of different plate tectonic reconstructions. Here, we use the GPlates software (version 2.2), an open-source plate tectonic reconstruction and modelling environment (Boyden et al, 2011;Cannon et al, 2014;Gurnis et al, 2018;Müller et al, 2018), to compare two published plate tectonic models (Matthews et al, 2016;Nirrengarten et al, 2018). Although various reconstructions of the North…”
Section: Comparison Of Plate Tectonic Reconstructionsmentioning
confidence: 99%
“…However, because ShowEarthModel is designed for point cloud data, a volumetric viewing software such as ParaView (Henderson et al, ) or 3DVisualizer (Billen et al, ; Jadamec et al, ) would be needed for viewing and extracting isosurfaces from a gridded data volume for a given seismic tomography data set. Furthermore, although ShowEarthModel allows for viewing the time evolution of earthquake sequences, other open‐source software, such as GPlates (Cannon et al, ; Qin et al, ), would be used to view the time evolution of surface plate motions. Thus, it is up to the user to determine the optimal software or collection of software for a given three‐dimensional problem, and this will require trial and error, writing code to append or modify existing software, and/or generating a new program.…”
Section: Discussionmentioning
confidence: 99%